Brazil farmland price volatility in distinct production regions - Wohlenberg, Emerson (Kansas State University, 2014)
Land is a fundamental input in agricultural production and the factors affecting land prices are an important topic in agricultural economics research. The farmland market has several unique characteristics. Land price volatility can be a source of problems for farmers and investors, especially in periods of falling prices in locations far from markets where the impact of land price reductions is higher than in other locations. This study analyzes land price volatility in different geographical regions of Brazil. The hypothesis is that variation in land price increases with the distance to the market, indicating that land price changes will be more pronounced in areas far from markets and the effects of price cycles in land markets will increase as distance from the market increases. The results obtained in this research support the hypothesis that areas far from end markets are exposed to greater changes in land prices and those same areas are more susceptible to price cycles. The effect on price volatility was also stronger in periods of land price declines. These regions have greater incentives for expansion and investment in periods of land price increase and greater risks of disinvestment and failure in periods of land price contraction. It is difficult to predict when a cycle of expansion or crisis will start or finish, but the present study helps to understand the effects of increases or decreases in land prices when such an event occurs.
Keywords: Brazil; Price volatility; Land price; Logistics; Distance to market; Von Thuen Theory; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Commerce-Business (0505)